2014
DOI: 10.1111/nyas.12363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic, processing, or product formulation changes on efficacy and safety of probiotics

Abstract: Commercial probiotic strains for food or supplement use can be altered in different ways for a variety of purposes. Production conditions for the strain or final product may be changed to address probiotic yield, functionality, or stability. Final food products may be modified to improve flavor and other sensory properties, provide new product formats, or respond to market opportunities. Such changes can alter the expression of physiological traits owing to the live nature of probiotics. In addition, genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 91 publications
1
64
0
Order By: Relevance
“…Growth conditions, growth substrates, cryoprotectants, product formulation, processing, and storage conditions may result in detectable changes in genes via mutations and genome rearrangements, gene expression patterns, and metabolic output, as reviewed by Sanders et al (2014). Such changes may affect functionality, for example, fermentation improvement strategies for yeast (Donalies et al, 2008) that include sugar-induced metabolic adaptations influencing wine quality (Erasmus et al, 2003).…”
Section: Cultures With Established Histories Of Safe Use For Intendedmentioning
confidence: 97%
See 1 more Smart Citation
“…Growth conditions, growth substrates, cryoprotectants, product formulation, processing, and storage conditions may result in detectable changes in genes via mutations and genome rearrangements, gene expression patterns, and metabolic output, as reviewed by Sanders et al (2014). Such changes may affect functionality, for example, fermentation improvement strategies for yeast (Donalies et al, 2008) that include sugar-induced metabolic adaptations influencing wine quality (Erasmus et al, 2003).…”
Section: Cultures With Established Histories Of Safe Use For Intendedmentioning
confidence: 97%
“…The potential effects of genetic, processing, and formulation changes on probiotic functionality and safety were reviewed by Sanders et al (2014). They concluded that it is very unlikely that a microorganism maintained in pure culture, with a history of safe use, would suddenly become unsafe as a result of mutation, production changes, or delivery format changes.…”
Section: Cultures With Established Histories Of Safe Use For Intendedmentioning
confidence: 99%
“…Comparisons of data from human studies have indicated that probiotic delivery matrices, including dairy products, can influence probiotic intestinal survival and persistence (1). Remarkably, however, only a single human study and a few animal studies have compared the impacts of different carrier matrices or food product formulations on the capacity of probiotics to influence health (1,2). Evidence from preclinical animal studies indicates that fermented milks might augment probiotic efficacy, although this has yet to be systematically investigated.…”
mentioning
confidence: 99%
“…Dairy products are the most popular food matrices for probiotic strains, and numerous clinical trials examining probiotic efficacy have used yogurt or (fermented) milks as carriers of probiotics to the intestine (1)(2)(3). Comparisons of data from human studies have indicated that probiotic delivery matrices, including dairy products, can influence probiotic intestinal survival and persistence (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation